Quality of services in higher education and its impact on student satisfaction and degree of their loyalty - A study on the students of the Faculty of Administrative and Financial Sciences at Taif University - - Abu Malih, Awad bin Omar; Al Siddiqui, Abdul Rahman Ghassan (Journal of Economic, Administrative and Legal Sciences, 2018)
The aim of this research is to identify the quality of services at Taif University and its impact on student satisfaction and degree of loyalty. The sample was used in the HEdPERF scale to collect data. The sample size was 534 students from the Faculty of Administrative and Financial Sciences at Taif University, 305 of whom were students and 229 female students. Structural Equation Models (SEM) Through AMOS software for data analysis, model evaluation and hypothesis testing. The results indicated that the quality of services in the college - from the point of view of the students - got a general average (3.2). The dimensions of the administration of the university and members of the teaching staff came (in second place and their average arithmetic (2.7), and all of which are of medium degree. The dimension of the university facilities obtained an average of (2.59) with a grade of (disagree) and the dimension of satisfaction of the students averaged (2.7). Finally, the dimension of the students’ loyalty obtained the lowest average of (1.59), with a (very weak) grade, that there is no relationship between student satisfaction and loyalty. The study also showed that student satisfaction has a partial mediation on the quality of services offered by Taif University and students’ loyalty (0.39-). In the light of the results of the study, a number of recommendations and proposals were presented to raise the quality of services, increasing their satisfaction and deepening their loyalty to their universities, their homeland and their nation.